(untitled) (Journal of the College of Basic Education, 2023)
In the name of God, and prayers and peace be upon the Messenger of God, and praise be to God, Lord of the worlds. We praise Him, seek His help, seek guidance from Him, and seek His forgiveness. We seek refuge in God from the evils of ourselves and from the evils of our deeds. As for after This research includes an important religious jurisprudential issue in the Muslims’ faith and their lives, which is (returning peace during prayer), and the rulings it contains, which every Muslim, male and female, must understand what it means. The issue, as for the life of the author, was based in his statement of his life on some of his published scholarly works and on manuscripts of him and other scholars. Two topics, the first topic: introducing the author’s life, and it included six demands, the first requirement: his name and lineage, the second requirement: his surnames and his family, the third requirement: his birth and death, the fourth requirement: his travels, the fifth requirement, his elders and disciples, and the second topic: introducing the manuscript, the first requirement Description of the manuscript copies, the second requirement: the name of the manuscript and documenting its attribution to its author, and the third requirement: methodology in the investigation. And the third topic: is the verified text, from the manuscript (Muhammadiyah issues in the necessary religious issues by Sheikh Abdullah bin Saleh Al-Samahiji), a question ((If a Muslim says, for example: Good evening, and the listener prays, then what does he respond to, if he does not respond to him Jealous) The purpose of my research is for a Muslim to know what is the ruling on returning peace in prayer - and I do not hide from you that delving into religious issues is a vast matter, and a vast sea, and it is our duty as Muslims and researchers to understand its parties and to learn the fundamentals of our religion, and from here the idea came with the idea of my research to reach my message For everyone who wants to benefit and learn more about his religion, I ask God that my research will be of benefit, and that it will benefit everyone who reads it, researcher or otherwise, and that our Lord will reward you and us